1973
DOI: 10.2134/agronj1973.00021962006500020027x
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Reflectance Hypothesis for the Pathway of Solar Radiation Through Leaves1

Abstract: The Willstätter and Stoll theory explains leaf reflectance as critical or total reflection of light at cell wall‐air interfaces of spongy mesophyll tissue, and is based on observations of the spectral properties of leaves in the visible wavelengths. Our data, obtained in the 0.72 to 1.3 μm (reflective infrared) wavelengths, showed that unexpectedly high levels of reflectance occurred from palisade tissue and from dehydrated leaves that had collapsed internal structures. A modification of the Willstätter‐Stoll … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(28 citation statements)
references
References 7 publications
0
27
0
1
Order By: Relevance
“…Changes in leaf structure have been observed to influence NIR in other vegetation types including herbaceous plants [49] and deciduous broadleaf trees [26]. High temperatures, such as those resulting from fires, can create structural deformations in leaf cell walls [19].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in leaf structure have been observed to influence NIR in other vegetation types including herbaceous plants [49] and deciduous broadleaf trees [26]. High temperatures, such as those resulting from fires, can create structural deformations in leaf cell walls [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the NIR beyond 750 nm, the reflectance values are not related to concentrations of wavelength-dependent absorbing pigments, but might change because senescence as well as biotic (pests, weeds, disease, fungi) and abiotic constraints (drought, floods, high light intensity, chilling, mineral deficiency, ozone) alter the internal structure of the foliage and/or the water content (Carter 1991;Estep et al 2005;Hatfield et al 2008;Jackson 1986;Maas and Dunlap 1989;Sinclair et al 1973;Slaton et al 2001). This means that any spectral change becoming apparent might give clues to the plant's stress condition and/or senescence.…”
Section: Crop Marks and Related Plant Reflectancementioning
confidence: 99%
“…Later Sinclair et al (1973) demonstrated that the high level of reflectance in the 720-1300 nm spectral region cannot be explained ?y the laws of reflection and transmission accepted in geometrical optics, which describe the radiative transfer at the cell wall -air interfaces in the spongy mesophyll tissue. The assumption that transmission and reflection from the cell walls is diffuse as defined by Lambert's cosine law will be in better agreement with experimental data.…”
Section: Soomentioning
confidence: 99%